The effect of new raw materials on pellet prices - Porsö, Charlotta (SLU/Dept. of Energy and Technology, 2010)
As demand for renewable energy is increasing rapidly, the market for biomass pellets is expected to continue to grow in the near future. Most of the new raw materials that are discussed for pellet production have one thing in common; the production costs will increase compared to using traditional raw materials such as sawdust and planer shavings. The aim of this thesis is to investigate to what degree increased use of new raw materials for pellet production will affect the general pellet prices in Sweden and to survey what plans Swedish pellet producers have concerning new raw materials.